POWER OF SHARING SUMBER DAYA KELAUTAN REPUBLIK INDONESIA - Vinata, Ria Tri (Faculty of Law, University of Muhammadiyah Malang, 2016)
Maritime and marine development targets are very realistic considering the position of Indonesia is geographically located and has a comparative advantage because it is very close to the world market. On the other hand, Indonesia is located in the tropics with thousands of islands have a wealth and maritime and marine resource potential is very large. Awareness of the protection and preservation of the marine environment began to grow among the countries participating in the Convention; especially regarding the exploitation of natural resources is carried out on a large scale in the marine environment. Especially for marine areas that are still in dispute, the power of sharing activity is the distribution of marine resources with the agreement Joint exploitation the original problem as a potential source of conflict, transformed and directed into a source of cooperation. Such cooperation generally includes the exploration, exploitation, and sharing of benefits derived from the exploitation of natural resources in the region for the parties.